Contemporary Issues and Prospects towards Effective Implementation of Revenue Allocation in Nigeria - Ibeme, Patricia Nwamaka; Taiwo, Abimboye Julius; Madu, Mavis; Atuegbu, Chinenye Miriam; Ibeme, Arinze Yves (NIU Journal of Humanities, 2023)
The study examined the contemporary issues and prospects towards effective implementation of revenue allocation in Nigeria. Three research questions guided the study. The study adopted a descriptive survey research design. The population of the study comprised 288 budget Officers under the Federal Ministry of Finance. The instrument for data collection was structured questionnaire developed by the researchers: Implementation of Revenue Allocation Questionnaire (IRAQ). The instrument was face validated by three experts, two from the Department of Public Administration, National Opening University of Nigeria, Abuja Study Centre and one from the Department of Public Administration and Local Government Studies, Faculty of Social Sciences, University of Nigeria, Nsukka. The internal consistency estimates for the structured questionnaire items were established using Cronbach Alpha techniques of estimating reliability which yielded an overall reliability co-efficient of 0.84 indicated that the instrument was reliable for the study. Data were collected by three research assistants using direct delivery and retrieval technique. Mean and Standard Deviation were used to answer the research questions. The findings of the study revealed the contemporary issue of revenue allocation and identified challenges which embedded as outlining prospects for it. The findings of the study also revealed in a bid strategies to resolve the controversial issues surrounding the contentious revenue allocation in Nigeria, a high level of fiscal decentralization is require replacing the unfair revenue sharing formula currently on operations. Based on the findings, among the recommendations were that revenue formulae for revenue sharing should be guided by national interest, which should take precedence over individual or primordial attention and reactions. Keywords: Contemporary issues, prospects, revenue, revenue allocation, revenue formula